RAS-Selective Lethal 3-Induced Ferroptosis Promotes the Antitumor Efficiency of Anti-Programmed Cell Death Protein 1 Treatment in Colorectal Cancer - Lu, Shiyv; Yao, Zhilu; Cheng, Qing; Wu, Jianping; Jiang, Yuanye; Lin, Hui (Turkish Journal of Gastroenterology, 2024)
Background/Aims: Anti-programmed cell death protein 1 (PD-1) treatment has exhibited clinical benefits in colorectal cancer (CRC). However, the low response rate of CRC to immunotherapy is an urgent problem that needs to be solved. Materials and Methods: MC-38 tumor cells was challenged subcutaneously in the flank of 7-week-old male C57BL/6 mice. The mice were randomly divided into 3 groups, and 200µg/mouse anti-PD-1 antibody and 100 mg/kg RAS-Seletive Lethal 3 (RSL) or phosphate buffer saline (PBS) were intraperitoneally injected every 2 days. The expression of oxidative stress and ferroptosis-related genes was measured by Western blotting, real-time reverse transcription-polymerase chain reaction, Prussian blue staining, and enzyme-linked immunosorbent assay. Results: Anti-PD-1 treatment-unresponsive tumors showed stronger immunosuppression than responsive tumors. Notably, the responsive tumors showed higher levels of H2O2 and reactive oxygen species, both of which could impair the antitumor effect of cytotoxic CD8+ T cells. The anti-PD-1 treatment-responsive tumors showed a higher expression of pro-ferroptosis genes and Fe2+ accumulation than those of anti-PD-1 nonresponsive tumors, indicating the potential role of ferroptosis in the efficacy of anti-PD-1 treatment. In MC-38 syngeneic tumor model, (1S, 3R)‐RSL3 (RSL), a glutathione peroxidase 4 inhibitor, effectively promoted the antitumor effect of anti-PD-1 treatment in vivo. However, anti-PD-1 treatment did not affect the levels of ferroptosis-related genes in tumor model. Mechanistically, RSL treatment significantly upregulated the frequency of proliferating (ki67+) and cytotoxic (GZMB+) CD8+ T cells. Furthermore, the frequency of tumor neoantigen-specific interferon (IFN)-γ CD8+ T cells showed a significant increase after RSL plus anti-PD-1 treatment. Conclusion: RSL may be a promising drug for potentiating the antitumor efficiency of anti-PD-1 treatment in CRC. Cite this article as: Lu S, Yao Z, Cheng Q, Wu J, Jiang Y, Lin H. RAS-Selective Lethal 3-induced ferroptosis promotes the antitumor efficiency of anti-programmed cell death protein 1 treatment in colorectal cancer. Turk J Gastroenterol. 2024;35(4):288-298.